Complete mitochondrial genome of the great seahorse Hippocampus kelloggi Jordan & Snyder, 1901 (Gasterosteiformes: Syngnathidae). (4th March 2017) - Cheng, Rubin; Liao, Guanghui; Ge, Yuqing; Yang, Bo; Zhang, Guangji
Abstract: In this study, the complete mitogenome sequence of great seahorse Hippocampus kelloggi (Gasterosteiformes: Syngnathidae) has been amplified and sequenced employing the polymerase chain reaction-based method. The total length of mitochondrial DNA is 16 536 bp and includes 13 protein-coding genes, two ribosomal RNA, 22 transfer RNA genes, and a control region. The mitochondrial gene arrangement of H. kelloggi was similar to that observed in most vertebrate creatures. The overall base composition of H. kelloggi is 32.19% for A, 23.68% for C, 29.30% for T, and 14.82% for G, with a slight AT bias of 61.49%. Phylogenetic analyses based on complete mitochondrial genome sequence showed that H. kelloggi has a close genetic relationship to H. reidi, H. ingens, and H. kuda .